โครงสร้างของสังคมพืชและความหลากหลายชีวภาพของพืชที่กำลังฟื้นตัวจากสวนวนเกษตรยางพาราในจังหวัดสงขลา สตูล และพัทลุง - สาระ บำรุงศรี (มหาวิทยาลัยสงขลานครินทร์, 2022)
Although rubber plantations cover large area of Thailand, especially in the South, only a few rubber plantations keep naturally successional native vegetation within them. The present study has an objective to determine species composition and vegetation structure of such native vegetation. Plots were set and all trees with diameter of at least 1cm were identified and measured in three study sites including Korhong Hill, Payang (Songkhla) and Tamod (Patthalung). Important Value Index (IVI) which represents plant performance in terms of density, frequency, and basal area were derived for each site. In Korhong Hill, Mesua kunstleri (King) Kosterm, Microcos tomentosa Sm.) Syzygium lineatum (DC.) Merr.& L.M. Perry, Barringtonia macrostachya Kurz, Streblus taxoides (Heynes) Kurz, Crypteronia paniculata Blume are plants with highest IVI. Microcos tomentosa Sm., Cleistanthus polyphyllus F.N. Williams, Mesua kunstleri (King) Kosterm, Callerya atropurpurea (Wall.) A.M. Schot contribute for most of IVI in Payang site. In Tamod, Garcinia merguensis Wight, Decaspermum parviflorum (Lam.) A.J. Scott, Syzygium grande (Wight) Walp., Garcinia cowa Roxb, Litsea grandis Hook f., Syzygium lineatum (DC.) Merr. & L.M. Perry have highest IVI. The different in IVI results from habitat characteristics, soil quality, and dispersal ability. Vegetation between Tamod and Korhong was the most similar (42.76 %). Simpson index of diversity was highest in Korhong whereas in Tomod and Payang, it was comparable. This diversity index positively relates to distance from forest and age of succession. Zoochory contribute 72-75% in each plant community, but relative density of zoochorous plants was highest in Tamod (85.17%), followed by Korhong (66.7%) and Payang (50.26%) which may be explained by distance to continuous forest. Farmers with flat, sand-dominated soil, shallow soil with low pH, and flood in some months can plant several plant species including Garcinia merguensis Wight, Decaspermum parviflorum, Syzygium grande, Garcinia cowa, Litsea grandis and Syzygium lineatum for biodiversity enrichment in rubber plantation, while farm in better soil quality can further grow tropical forest species such as Hopea odorata Roxb., Michelia champaca L., Aquiralia sp. and economic exotic plants such as Azadirachta excels (Jack) Jacobs. and Swietenia macrophylla King.